Advancing family theories - White, James M. 1946- (Thousand Oaks, California London SAGE, 2005)
Explores two contemporary theories of the family-rational choice theory & transition theory that illuminate what differing theories reveal about families. The book also discusses how meta-theories can assist in refining theory, & offers insight on the 'understanding versus explanation' debate
Title from title screen (viewed October 19, 2023
Includes bibliographical references and index
Description based on print version record
Keywords: Families -- Philosophy; Families -- Research; Sociology -- Methodology; Sociology -- Philosophy